Chaos in social and political phenomena: the drop of honey effect - Filipe, J. A. (2020)
Chaos theory has been first applied to natural sciences and then to the humanities and social sciences and, since the beginning, got rapidly a developing field. Chaos is extremely complex and difficult to be identified in the real world. Even using the workable information, it is possible, anyway, up to a certain extent, to find specific mathematical relationships for problems to be solved. In this study some issues are presented in order to work this subject in the humanities and social sciences.